“It’s Unfair” The Effect of Free Riding And Social Loafing of Group Discussion In Cooperative Learning - Burhanuddin Yasin; Omar Khalifa Burhan; Ika Apriani Fata; Faisal Mustafa; Endang Komariah (Proceedings of AICS - Social Sciences, 2021)
Cooperative learning has a long history in higher education, dating back thousands of years. Small groups are used in particular so that students can maximize their own and each other's learning. Cooperative learning, on the other hand, is more than just putting students in groups; it also involves adding fairness engagement into the group learning process. At Universitas Syiah Kuala, this study sought to determine the impact of free riding and social loafing on group conversation. Using genuine experimental design, a total of N=70 people were separated into one experimental class and one control class. The results revealed between the experimental group and the control group that in the experimental group, the subjects tended to rate and be judged by their group peers as optimum contributors (SCI = 1). This SCI of 1 means that group members contribute as they should, nothing more and nothing less. This indicates the absence of social loafing and free riding.Keywords: Cooperative learning, free riding, social loafing, group work.